2006
DOI: 10.1111/j.1601-183x.2006.00245.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of brain‐derived neurotrophic factor in relapsing–remitting multiple sclerosis

Abstract: Multiple sclerosis (MS) is a common, heterogeneous disorder of the central nervous system with a complex trait composed of both genetic and environmental factors. Recently, scientific interest has increased in defining factors that possibly contribute to brain functional plasticity; the results might be useful to assess the relationship between MS lesion burden and clinical events, as well as explaining the well-known phenotypic heterogeneity of the disease. In this study, we explored the effect of the Val66Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 41 publications
(60 reference statements)
2
24
2
1
Order By: Relevance
“…It is reasonable to assume that the Met66 is associated with lower secretion of BDNF, which could result in attenuation of the survival signal of BDNF, compared with the Val66. In accordance with this, individuals carrying the Met66 allele have been reported to have decreased brain structures (e.g., hippocampus) than those individuals who did not carry the allele [Pezawas et al, 2004;Szeszko et al, 2005;Agartz et al, 2006;Bueller et al, 2006;Ho et al, 2006;Nemoto et al, 2006;Frodl et al, 2007;Liguori et al, 2007]. Of note, we found that female individuals carrying the Met66 allele showed more widespread ageassociated volume reduction in the dorsolateral prefrontal cortices than male Met66 carriers [Nemoto et al, 2006].…”
Section: Discussionsupporting
confidence: 83%
“…It is reasonable to assume that the Met66 is associated with lower secretion of BDNF, which could result in attenuation of the survival signal of BDNF, compared with the Val66. In accordance with this, individuals carrying the Met66 allele have been reported to have decreased brain structures (e.g., hippocampus) than those individuals who did not carry the allele [Pezawas et al, 2004;Szeszko et al, 2005;Agartz et al, 2006;Bueller et al, 2006;Ho et al, 2006;Nemoto et al, 2006;Frodl et al, 2007;Liguori et al, 2007]. Of note, we found that female individuals carrying the Met66 allele showed more widespread ageassociated volume reduction in the dorsolateral prefrontal cortices than male Met66 carriers [Nemoto et al, 2006].…”
Section: Discussionsupporting
confidence: 83%
“…Conflicting information is also present in regards to the effects of Val 66 Met on T2 hyperintensity lesion load in multiple sclerosis, an index of prominent dysmyelination. The only investigation to examine a relatively large population (n ¼ 209) found that the Met allele was associated with diminished lesion load as compared with Val/Val (Zivadinov et al, 2007) , but this result has not been confirmed in smaller cohorts (Dinacci et al, 2011;Liguori et al, 2007). Nevertheless, T2 hyperintensities are not found in our samples and cannot explain our results.…”
Section: Bdnf Val 66 Met Effects On Dti Measures In Normalscontrasting
confidence: 56%
“…The MAO A promoter region polymorphism, the Val 158 Met COMT, and Val 66 Met BDNF polymorphisms were genotyped on the basis of previously described methods [5,16,17].…”
Section: Methodsmentioning
confidence: 99%